Fascism, comedy, and weak commitments in Nancy Mitford's Wigs on the Green. Issue 1 (2nd January 2020) - Murphy, Eliza
ABSTRACT: Occupying an ambiguous position in relation to the literary movements of the twentieth century, British writer Nancy Mitford (1904–1973) is most well-known for her postwar novels, The Pursuit of Love (1945) and Love in a Cold Climate (1949). However, her interwar novels published in the early years of her writing career offer the potential for fruitful readings. This article takes as its focus Mitford's 1935 novel Wigs on the Green, a romantic comedy revolving around a fascist pageant play. Through comedy, the novel critiques the aristocracy's engagement with radical politics, which it interprets as an effort to restore traditional ideals of Englishness. Wigs on the Green, like many of Mitford's novels, is characterized in its form and content by weak commitments which serve to generate the novel's laughter and critique: from the characters' naïve acceptance of fascism to the novel's subversion of the conventions of the romantic comedy. Wigs on the Green 's preoccupation with weak commitments is best revealed through a reading that positions Mitford as an "intermodern" writer, a framework I argue is attuned to weakness. Mitford's novel thus reveals the usefulness of intermodernism for reading and recovering women's comedy writing of the interwar years.